Effective Strategy of Madrasah Public Relations: Building Image and Encouraging Educational Program Innovation - Setiawan, Doni; Romlah; Septuri (Journal of Advanced Islamic Educational Management, 2025)
This study explores the implementation of public relations (PR) management in the development and execution of programs at Madrasah Tsanawiyah (MTs) Negeri 2 Bandar Lampung. The research highlights the vital role of PR in establishing effective communication between the school and its internal and external communities to enhance educational quality and institutional image. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation, and analyzed through data reduction, display, and conclusion drawing. Data validity was ensured using source triangulation. The findings reveal that PR management is implemented through four main components: (1) Planning—by conducting surveys, designing programs, and forming teams; (2) Organizing—by dividing tasks, coordinating responsibilities, and establishing clear workflows; (3) Evaluation—through regular assessments on a monthly, quarterly, and annual basis; and (4) Controlling—by agreeing on program models and using SWOT analysis. However, the study also found weaknesses, including the absence of a comprehensive written PR guideline and limited use of two-way communication in digital media for school promotion.